Well-posedness, blow-up phenomena and persistence properties for a two-component water wave system. (October 2015) - Guan, Chunxia; He, Huijun; Yin, Zhaoyang
Abstract: We first establish the local well-posedness for the Cauchy problem of a two-component water waves system in nonhomogeneous Besov spaces using the Littlewood–Paley theory. Then, we derive three new blow-up results for strong solutions to the system. Finally, we present two persistence properties for strong solutions to the system.